"I Belong Because It Wasn't Made for Me": Understanding Working-Class Students' Sense of Belonging on Campus. (29th July 2021) - Bettencourt, Genia M.
ABSTRACT: Sense of belonging has been used to gauge students' adjustment to and persistence within higher education. Social class is associated with sense of belonging and working-class students report lower levels than their middle- and upper-class peers. In this study, I examined how working-class students described their sense of belonging through a critical constructivist narrative inquiry of 24 working-class students across two public research institutions. I found that students developed academic and co-curricular spaces of connectedness to challenge the broader campus culture that they saw as catering to middle- and upper-class students. The same resources were supportive or unsupportive depending on students' circumstances. Belonging was viewed as something that students themselves created rather than was facilitated by institutions. Moreover, while participants expressed varying degrees of support, connectedness, and belonging, they rarely felt valued by institutions that exploited their labor or tokenized their presence under the guise of supporting diversity. Implications from this research suggest the need to revisit conceptualizations of sense of belonging while providing recognition of working-class contributions, increasing cultural competence, and developing additional structural supports for students.